Affirming and living with differences - Borght, Ed. A.J.F. van der, 1956- (Studies in Reformed Theology, 2006)
The multi-cultural society is under enormous pressure. Paradoxically, the globalization plans of modernity have resulted in a more fragmented world and ensuing violence. Instead of becoming uniform, individual character and differences have become more strongly emphasized. How can people live together and at the same time preserve their differences? How can variety be valued in a theological manner? These questions form the theme of this collection that consists of three sections. The South African reflections (Simon, Louw and Koopman) that consider living in the variety of a rainbow nation are followed by European experiences of Moluccan Christians in the Netherlands (Pattikayhatu), Western Muslims (van Bommel) and the Belgian modus vivendi (Van der Borght). The collection is completed by the theological reflections about the concept communio sanctorum (Le Bruyns), the Enlightenment's ideal of equality (van de Beek) and the unity of the church (Theron)..